ETIKA PENGUMPULAN DATA KONSUMEN MUSLIM DI ERA DIGITAL: TINJAUAN DARI PRINSIP HIFZ AL-MAL DAN MASLAHAH AMMAH - Abiseka Sahal Rizky Fauzi; Muhammad Za’im Musyaffa; Amanda Tri Utami (Taksasila Edukasi Insani, 2025)
This article discusses the ethics of collecting data on Muslim consumers in the digital era with reference to the principles of maqashid sharia, specifically hifz al-mal and maslahah 'ammah. The development of digital technology has changed the way consumers and businesses interact, but data collection practices often lack transparency and risk abuse. In this context, personal data protection is crucial to safeguard individual rights and prevent harm. This research aims to provide an ethical perspective rooted in Islamic values on data management, as well as recommend measures to improve consumer data protection.Keywords : Ethics, Data Collection, Muslim Consumer, Hifz al-Mal, Maslahah 'Ammah